Concurrent autoimmune and endocrine dysregulation in polycystic ovary syndrome - Halah Amer Abduljabbar; Majid Mohammed Mahmood; Methaq J. Al-Jbooriay; Manal Taha Al-obaidi (Middle East Fertility Society Journal)
Abstract Background Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, ovulatory dysfunction, and a polycystic ovarian morphology. Emerging evidence suggests that autoimmunity may contribute to PCOS pathogenesis. Methodology In this cross-sectional study, 100 women with PCOS and 78 age-matched healthy controls underwent clinical assessment, hormonal profiling (FSH, LH, LH/FSH ratio, total testosterone, AMH, prolactin, and thyroid hormones), and autoantibody measurement (anti‐ovarian (AoA), anti‐thyroid peroxidase (anti‐TPO), anti‐thrombopoietin [anti‐THPO], and anti‐GAD) using validated immunoassays. Results PCOS participants demonstrated higher BMI, hyperandrogenism, elevated LH/FSH ratio, increased AMH and prolactin levels, and mild thyroid hormone elevation. The autoantibody levels (anti-TPO, anti-THPO, anti-GAD, and AoA) were significantly higher in the PCOS (p < 0.05). ROC curve analysis identified anti-TPO (AUC = 0.90) and anti-GAD (AUC = 0.86) as strong discriminators. In the multivariate logistic regression, anti‐THPO (OR = 1.97 per ng/mL, p = 0.0052), anti‐TPO (OR = 1.48 per IU/mL, p = 0.048), and anti‐GAD (OR = 1.52 per ng/mL, p = 0.0046) remained independent predictors of PCOS. Correlation analysis revealed significant associations between the LH/FSH ratio and AMH (r = 0.300, p = 0.002), testosterone and anti‐TPO (r = 0.385, p < 0.001), and anti‐GAD and AMH (r =  − 0.251, p = 0.012). Conclusions Autoimmune markers coexist with classical endocrine abnormalities in PCOS patients. Incorporating targeted autoantibody screening may improve PCOS characterization and guide personalized management.